2018
DOI: 10.1212/wnl.0000000000005060
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker pattern of ARIA-E participants in phase 3 randomized clinical trials with bapineuzumab

Abstract: Baseline biomarkers largely do not predict risk for developing ARIA-E. ARIA-E was associated with significant longitudinal changes in several biomarkers, with larger reductions in amyloid PET and CSF p-tau and t-tau concentrations, and paradoxically greater hippocampal volume reduction and ventricular enlargement, suggesting that ARIA-E in bapineuzumab-treated cases may be related to increased Aβ efflux from the brain and affecting downstream pathogenic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
0
27
2
Order By: Relevance
“…Consequently, the gantenerumab data indicate that ARIA-E is not a prerequisite for large amyloid reductions. This result contrasts the data reported for bapineuzumab, in which there was a lack of change from baseline in the non-ARIA-E groups [36].…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, the gantenerumab data indicate that ARIA-E is not a prerequisite for large amyloid reductions. This result contrasts the data reported for bapineuzumab, in which there was a lack of change from baseline in the non-ARIA-E groups [36].…”
Section: Discussioncontrasting
confidence: 99%
“…1,15,23,24,39,41 When ARIA occur, 1) the severity of pre-existing underlying CAA pathology, 2) the displacement of Aβ from parenchymal plaques to the vessel walls, 3) the rapid disaggregation of Aβ at high doses of the drug, particularly in APOEε4 patients, may all play a key role in determining and/or sustaining the inflammatory and immune response. 19,23,[42][43][44] The contributing role of underlying CAA pathology finds further support in the acute and focal nature of WMHs in both CAA-ri and ARIA-E, 23,41 which present mainly in posterior occipital regions of the brain, where there is a likely higher CAA burden. 45,46 Of note, although ARIA-E presents in brain areas with extensive removal of Aβ on amyloid-PET, with a mechanism presumably involving microglial activation, 41 similar consistently large amyloid reductions have been observed also in patients without ARIA-E in open-label extension studies.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies revealed that aducanumab enhanced recruitment of microglia to amyloid plaques via engagement of Fcγ receptors. In a recent study on bapineuzumab (epitope: N-terminus Aβ1-5, IgG1 isotype) the authors demonstrated that Alzheimer's Related Imaging Abnormality-Edema (ARIA-E) was associated with larger reductions in amyloid PET, suggesting that in treated cases ARIA-E might be related to increased Aβ efflux from the brain [29]. In addition, higher dose of gantenerumab (epitope: N-terminus Aβ1-10 and central region Aβ18-27, IgG1 isotype) reduced amyloid load as measured by amyloid PET, which was indicative of successful target engagement in the brain [39].…”
Section: Discussionmentioning
confidence: 99%